2009
DOI: 10.1364/ol.34.001915
|View full text |Cite
|
Sign up to set email alerts
|

Rate-equation model for the loading-rate-dependent mechanoluminescence of SrAl_2O_4:Eu^2+,Dy^3+

Abstract: The mechanoluminescence (ML) of SrAl2O4:Eu2+,Dy3+ (SAO) phosphors was monitored as a function of its instantaneous loading rate, on which it was found to be strongly dependent. The effect of the loading rate on the ML of SAO was investigated in a systematic manner using rate equations involving the loading rate term. The rate equations and the experimental data matched well. We confirmed that the ML of SAO was created by the change in load rather than by the static load, and that the loading rate determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Changing of the surface as a result of movement of charged dislocations is believed to be responsible for pulsed ML whereas electrostatic interaction between the charged dislocations and filled electron traps has been reported to be responsible for continuous ML in the plastic region of II-VI semiconductors. [7][8][9][10] ZnS is a piezoelectric material, and piezoelectric materials have the property of converting stress (force) into electrical (or voltage) signals. When stress is applied to a piezoelectric layer, electrical charges are induced at the top and bottom of the layer.…”
Section: Introductionmentioning
confidence: 99%
“…Changing of the surface as a result of movement of charged dislocations is believed to be responsible for pulsed ML whereas electrostatic interaction between the charged dislocations and filled electron traps has been reported to be responsible for continuous ML in the plastic region of II-VI semiconductors. [7][8][9][10] ZnS is a piezoelectric material, and piezoelectric materials have the property of converting stress (force) into electrical (or voltage) signals. When stress is applied to a piezoelectric layer, electrical charges are induced at the top and bottom of the layer.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it was found that the mechanically driven luminescence of ZnS:Cu was available only when this phosphor was combined with the polydimethylsiloxane (PDMS) matrix. On the contrary, other well-known ML phosphors such as SAO and ZnS:Mn gave a promising ML, when hard matrix materials were adopted, [1][2][3][4][5][6][7][8][9] but no luminescence when a soft PDMS was adopted as a matrix material. It is evident that the conventional ML materials exhibit the strongest ML owing to the stronger load transfer when the rigid matrix materials were adopted, i.e., SAO and ZnS:Mn gave a promising ML with epoxy resin and acrylic resin but no luminescence with PDMS.…”
Section: -15mentioning
confidence: 92%
“…A similar double-peak response has also been observed for the case of ZnS:Mn film under a compressive load of 500 N. 25 However, those double peaks were produced by a controlled static loading and an abrupt release in a relatively long time scale (∼20 s). It was a typical loading rate dependent conventional ML, 6 which differs from the dynamic cyclic behavior. The ML in the present case may be only due to the soft friction-induced electric field, which is high enough to excite electroluminescence.…”
Section: -15mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, many other researchers have also started to develop novel ML materials, sensors, and diagnostic methods. (12)(13)(14) Meanwhile, the Trillion Sensors Universe, in which over trillions of sensors cover an entire society, has been starting. The number of sensors in the universe will be 100 times the present requirement with 150 new sensors per year for each of the 7 billion people worldwide.…”
Section: Introductionmentioning
confidence: 99%